2007
DOI: 10.1177/1087054706289941
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Concordance of Measures Used to Diagnose Adult ADHD

Abstract: Results suggest that self- and collateral reports of inattentive and hyperactive/impulsive symptoms are highly correlated, as are self-report measures and diagnostic interviews. Additionally, it was found that probands report more inattentive symptoms than collaterals in both childhood and currently. Potential implications for the assessment of adult ADHD are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 40 publications
1
35
0
1
Order By: Relevance
“…Correlations between tasks and self-report instruments, or between different tasks purportedly measuring the same construct, are generally modest (Toplak, West, & Stanovich, 2012; Decker, Hill, & Dean, 2007; see Wostmann et al, 2013 for an exception to this in the measurement of inhibitory control and Belendiuk, Clarke, Chronis, & Raggi, 2007 for a discussion of correlation in measurement of adult ADHD). For example, self-report instruments can be problematic because those with higher executive dys-function may be less attuned to their own emotion and cognitive control capacity and they may self-rate their emotion and cognitive control capacity as high but perform poorly on neuropsychological tasks (Sølsnes, Skranes, Brubakk, & Løhaugen, 2014).…”
Section: Implications For Programs Policy and Researchmentioning
confidence: 99%
“…Correlations between tasks and self-report instruments, or between different tasks purportedly measuring the same construct, are generally modest (Toplak, West, & Stanovich, 2012; Decker, Hill, & Dean, 2007; see Wostmann et al, 2013 for an exception to this in the measurement of inhibitory control and Belendiuk, Clarke, Chronis, & Raggi, 2007 for a discussion of correlation in measurement of adult ADHD). For example, self-report instruments can be problematic because those with higher executive dys-function may be less attuned to their own emotion and cognitive control capacity and they may self-rate their emotion and cognitive control capacity as high but perform poorly on neuropsychological tasks (Sølsnes, Skranes, Brubakk, & Løhaugen, 2014).…”
Section: Implications For Programs Policy and Researchmentioning
confidence: 99%
“…Then the parents were interviewed by a child and adolescent psychiatrist using the ADHD section of the kiddie schedule for affective disorders and schizophrenia-present and lifetime version (K-SADS-PL) (Chambers et al, 1985). K-SADS has been used to evaluate ADHD symptoms in adults (Biederman et al, 1993;McGough et al, 2005;Belendiuk et al, 2007). To obtain the history of childhood ADHD and to evaluate the current ADHD symptoms, one of the family members who was aware of the patient's childhood history was also interviewed.…”
Section: Diagnostic Instrumentsmentioning
confidence: 99%
“…16 The criteria were created based on children 17 without validation in adults, 18 have been called too restrictive for the adult population, 19 and leave out symptoms such as procrastination, poor motivation, and time-management difficulties. 15 One study found that the DSM-IV criteria did not adequately distinguish between adults with ADHD and adults without ADHD, 20 and only approximately one third of adults diagnosed with ADHD actually meet the DSM-IV ADHD criteria.…”
mentioning
confidence: 99%